Fabriquer un escalier : « La Scala d’Oro », une collection pour l’enfance en Italie dans les années 30 - Elisa Rebellato (Strenae)
"La Scala d'Oro" is one of the most famous Italian Children’s Book collections. Created by two intellectuals, Fernando Palazzi and Vincenzo Errante, who were responsible for the choice of texts and authors, it was published in Turin by UTET between 1932 and 1936; it totaled 93 volumes divided into eight series, each one aimed at a different age group. The archives of Fernando Palazzi and those of some of the collection’s authors—such as Eugenio Treves and Marino Moretti—allow us to study in detail the evolution of this ambitious publishing project. These archives also reveal the control exercised by the directors over their authors, and the active part they played in designing the works themselves.